Beastly Tales for the Anthropocene: Review of Nayanika Mathur, Crooked Cats: Beastly Encounters in the Anthropocene - Bhattacharjee, Paloma (Humanimalia, 2023)
Nayanika Mathur. Crooked Cats: Beastly Encounters in the Anthropocene. Animal Lives. Chicago: University of Chicago Press, 2021. xiv + 208 pp., 16 halftones. $27.50 (pb).